Partial characterization of the pigments produced by the marine-derived fungus Talaromyces albobiverticillius 30548. Towards a new fungal red colorant for the food industry - Venkatachalam, Mekala; Zelená, Miroslava; Cacciola, Francesco; Česlová, Lenka; Girard-Valenciennes, Emmanuelle; Clerc, Patricia; Dugo, Paola; Mondello, Luigi; Fouillaud, Mireille; Rotondo, Archimede; Giuffrida, Daniele; Dufosse, Laurent (Academic Press (Elsevier), 2018)
The interest about red color in the food industry has been growing because of its wide application in variety of foods and beverages and also due to the carcinogenic and teratogenic effects of some synthetic colorants. Many ascomycetous fungi naturally synthesize and secrete pigments and thus provide readily available additional and/or alternative sources of natural colorants that are independent of agro-climatic conditions. Some species of Talaromyces produce large amounts of Monascus-like azaphilone red pigments without any toxins. In this study, Talaromyces albobiverticillius 30548 was isolated from the outer slope of the coral reef of the Reunion Island, Indian Ocean. The biosynthesized intracellular and extracellular pigments were extracted by successive cold extractions or by single solvent extraction methods The pigments were then analyzed by HPLC-PDA-ESI/MS system in positive and negative ionization modes. Twelve different compounds were detected and four were tentatively identified as Monascus-type pigments, based on the results obtained and the available literature. In particular, N-threonine-monascorubramine, N-glutaryl-rubropunctamine and PP-O were tentatively identified; further, this work reports for the first time on the PDA, MS and NMR characterization of the here named as N-GABA-PP-V (6-[(Z)-2-Carboxyvinyl]-N-GABA-PP-V) pigment bearing a cis configuration at the C10-C11 double bond, in Talaromyces albobiverticillius 30548.
Charakterizace pigmentů produkovaných plísní Talaromyces albobiverticillius 30548. K novému červenému barvivu pro potravinářský průmysl.
Keywords: Filamentous fungus; Talaromyces albobiverticillius; Matine; derived food colorant; Red colored pigments; Azaphilone; HPLC-MS; NMR; Talaromyces albobiverticillius; potravinářské barviva; azaphilony; HPLC-MS; NMR, červená barviva